KORELASI PAPARAN IKLAN ROKOK DAN SPONSORSHIP TERHADAP PENINGKATAN PREVALENSI PERILAKU MEROKOK REMAJA DI KOTA PADANG - Muhammad Ath Thaariq; Ringgo Eldapi Yozani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Adolescent smoking behaviour is currently experiencing a drastic increase. Data shows that West Sumatra is one of the cities that has the highest number of teenage smokers, where this study aims to determine the relationship between exposure to cigarette advertising and cigarette sponsorship on the prevalence of adolescent smoking behaviour in Padang City with 5 schools being the object of research which happened to have been given counseling on the dangers of smoking from the surrounding health centre. This study used quantitative methods with a cross sectional approach. Data analysis used univariate analysis, bivariate with chi-square test and smoking prevalence and multivariate and validity and reliability tests to see the feasibility of the data. The results of the study there is a picture of exposure to advertising resulting in adolescents smoking as many as 58 students and cigarette sponsorship 80% of students support. As well as the correlation between exposure to cigarette advertising on adolescent smoking behaviour in Padang City with a p value of 0.000 (OR 3.086 (1.477-4.476), 4.631 (1.761-6.397), 5.690 (3.949-8.596)) and cigarette sponsorship with (OR 4.250 (1.674-10.787) and 1.619 (1.199-2.186)). While based on multivariate results with a POR value of 3.956 there is an influence of exposure to cigarette advertising on adolescent smoking behaviour. Keywords: cigarette advertising exposure, sponsorship and prevalence of adolescent smoking behaviour